Selecting Energy-Efficient LED Retrofits with Optimal Color Qualities for New and Refurbished Buildings - Irena Fryc; Maciej Listowski; Robert Supronowicz; Christophe Martinsons (Energies)
This study carried out a literature search and selection in accordance with the PRISMA 2020 protocol to conduct a complete review of the literature describing the electrical, photometrical, and colorimetric parameters of LEDs. Based on it, a significant research gap was found in the field of LED-based lighting retrofits. We prove that there is a lack of publications indicating the relationship between the energy consumption of LED retrofits and user preferences concerning the quality of lighting. This article presents an effective new method for selecting LEDs to retrofit typical 3000, 4000, and 6500 K fluorescent lighting installations in buildings. It is shown that when selecting an LED replacement for a fluorescent source, consideration of the classically used parameters in the field of lighting technology to describe the quality of white light, specifically correlated color temperature and the color rendering index, is insufficient. We demonstrate that energy efficiency and the color preference criteria for retrofitted LEDs must be considered and balanced with the potential impact on circadian rhythms as assessed by the melanopic daylight efficacy ratio. This research proves that LED replacements with the best color preference properties (P1 class in the CPC classification of ANSI/IES TM30-20 method) correspond to the least energy-efficient light sources.